Mahy - a family of cars : the tranquil beauty of unique classic cars - Mahy, Michel; Rawoens, Wouter, 1963- (Tielt : Lannoo, 2021)
Row after row of disused factory halls in the rolling hills of Belgian Hainaut. Nothing is made here, except motoring history. There is an all-pervading smell of rust and motor oil. In the dusty interior, hundreds of vintage cars stand bumper to bumper. Some of them are propped up at jaunty angles on axle stands. Most lean drunkenly on the rubber of their long-flat tyres. Legendary models, ordinary family cars, flamboyant old bangers, long-forgotten jalopies, each with its own story to tell. As a whole, they form the raison d'être of the Mahy family from Ghent: three generations of dedicated collectors, who over the years have gathered together the largest collection of old-timers in the world.00This book sheds light on this silent cavalcade of unique vehicles. Some (very) old; some not so old. Some backlit; some spotlit. All with fascinating stories of the past etched into their rear-view mirrors. Stories of glory and loss, of death-defying rides over dangerous roads, of a never-ending search to find ultimate beauty on four wheels. Stories that have been told for generations in the Mahy family, a family of cars.
Industrieel erfgoed: Gent & Oost-Vlaanderen (rubricering Patrick Viaene)
Keywords: Mahy family; Mahy family; Antique and classic cars -- Pictorial works; Antique and classic cars -- Private collections -- Belgium -- Ghent; Antique and classic cars; Belgium -- Ghent; Pictorial works